Evolution of Olfactory Functions on the Fire Ant Social Chromosome. (18th September 2018) - Cohanim, Amir B; Amsalem, Etya; Saad, Rana; Shoemaker, DeWayne; Privman, Eyal
Abstract: Understanding the molecular evolutionary basis of social behavior is a major challenge in evolutionary biology. Social insects evolved a complex language of chemical signals to coordinate thousands of individuals. In the fire ant Solenopsis invicta, chemical signals are involved in the determination of a polymorphic social organization. Single-queen (monogyne) or multiqueen (polygyne) social structure is determined by the "social chromosome, " a nonrecombining region containing ∼504 genes with two distinct haplotypes, SB and Sb. Monogyne queens are always SBB, while polygyne queens are always SBb. Workers discriminate monogyne from polygyne queens based on olfactory cues. Here, we took an evolutionary genomics approach to search for candidate genes in the social chromosome that could be responsible for this discrimination. We compared the SB and Sb haplotypes and analyzed the evolutionary rates since their divergence. Notably, we identified a cluster of 23 odorant receptors in the nonrecombining region of the social chromosome that stands out in terms of nonsynonymous changes in both haplotypes. The cluster includes twelve genes formed by recent Solenopsis -specific duplications. We found evidence for positive selection on several tree branches and significant differences between the SB and Sb haplotypes of these genes. The most dramatic difference is the complete deletion of two of these genes in Sb. These results suggest that the evolution of polygyne social organization involved adaptations in olfactory genes and opens the way for functional studies of the molecular mechanisms underlying social behavior.